Prohibition of Marrying Maternal Cousins from the Perspective of Islamic Law - Gunawan, Hendra; Rahmita, Rahmita; Nafian, Zidni Ilman (Samara: Journal of Islamic Law and Family Studies, 2025)
The prohibition of marriage between first cousins by the community in the village does not include women who are forbidden to marry. However, there are strong customary laws that have been passed down from generation to generation by ancestors that prohibit marriage between first cousins. This is due to strong family ties and concerns that the offspring will suffer from severe physical and mental disabilities. Using a descriptive qualitative research method with an empirical legal approach, the data analysis used empirical methods such as interviews, field notes, and other personal documents. The primary data sources were ninik mamak, buya/ustadz, and wali nagari. Meanwhile, the secondary data sources were theses, journals, books, and other materials related to the discussion. The Rumbai River community's understanding of the prohibition against marrying cousins from the same mother is due to several reasons, namely: because it has become a rule or custom in the area; to avoid conflict between communities within the clan; and to avoid unwanted genetic similarities. The prohibition against marrying first cousins is a deeply ingrained custom or culture. If someone is found to have married a first cousin, they will be expelled from the community. From an Islamic legal perspective, marrying a cousin is not prohibited, as they are not considered mahram or people who are forbidden to marry. However, it is also important to note that the Prophet Muhammad (peace be upon him) recommended that Muslims marry people who are not too closely related. This recommendation may be intended to expand family ties and avoid the possibility of breastfeeding.